Attitudes of cystic fibrosis patients and their parents towards direct-to-consumer genetic testing for carrier status. (March 2015) - Janssens, Sandra; Kalokairinou, Louiza; Chokoshvilli, Davit; Binst, Carmen; Mahieu, Inge; Henneman, Lidewij; De Paepe, Anne; Borry, Pascal
Background: An increasing number of direct-to-consumer (DTC) genetic testing companies have started offering tests for carrier status of autosomal recessive disorders.Materials & Methods: A written questionnaire was administered to 47 patients and 65 parents of children with Cystic Fibrosis (CF), a common severe autosomal recessive disorder, to assess their views about the offer of DTC carrier tests. All participants were recruited from a CF patient registry in Belgium.Results & Conclusion: We found that very few patients and parents were aware of the offer of DTC genetic testing for carrier status, and were generally skeptical. A strong preference for the healthcare system over commercial companies as the provider of the test was observed. However, many participants believe people should have a right to access DTC genetic tests provided by commercial companies.